An assessment of the effects of deforestation on biodiversity in OJO local government area of Lagos State, Nigeria - Oga Omoyemi Azeez (Global Journal of Ecology - Peertechz Publications, 2023)
This study assessed the impact of deforestation on biodiversity in the Ojo Local Government Area of Lagos State, Nigeria. Three hundred respondents were randomly selected from ten communities of the local government. Primary data were collected with a structured questionnaire in order to address the objectives of the study. Both descriptive and inferential statistics were used to analyze the data collected. Respondents in the study area affirmed that there is deforestation activity in the local government and at a high rate. The study revealed that poverty is the major driver of deforestation in the study area, followed by urbanization and industrialization, while education level is the least factor responsible for deforestation. It was also uncovered that deforestation aids displacement and loss of plant and animal species from their natural habitats. It also leads to the loss of indigenous people's homeland, contributes to erosion and infertility, and results in the loss of plants and animal species used for research, economic, and medicinal purposes. Chi-square analysis revealed that there is a significant relationship between deforestation and displacement of both plants and animal species in the study area. Considering the high rate and effects of deforestation in the study area, it was then recommended that the elected chairman of Ojo Local Government in partnership with various community leaders of the study halt deforestation activity for five to ten years, for the forest to rebound. Raise awareness among the people about the impact of their actions on the forest and initiate comprehensive tree-planting programs with stringent monitoring.